2020
DOI: 10.1038/s41467-020-18482-w
|View full text |Cite
|
Sign up to set email alerts
|

Wide range zero-thermal-quenching ultralong phosphorescence from zero-dimensional metal halide hybrids

Abstract: Materials with ultralong phosphorescence have wide-ranging application prospects in biological imaging, light-emitting devices, and anti-counterfeiting. Usually, molecular phosphorescence is significantly quenched with increasing temperature, rendering it difficult to achieve high-efficiency and ultralong room temperature phosphorescence. Herein, we spearhead this challenging effort to design thermal-quenching resistant phosphorescent materials based on an effective intermediate energy buffer and energy transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
163
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 222 publications
(166 citation statements)
references
References 62 publications
3
163
0
Order By: Relevance
“…As a new generation of luminescent materials, emerging metal halide perovskites/perovskite derivatives with unique photoluminescence (PL) properties have attracted growing research interests. [ 14–23 ] Many of high‐efficiency blue, green, yellow, red, and even single‐phase white emitting metal halides have been explored, in which the PL wavelength covering the entire visible light region can be controlled by assembling alkali metal cations or organic cations with different metal halide species. [ 24,25 ] Meanwhile, thanks to the low‐temperature solution processable characteristic and the great adjustability of emission, metal halides have also been considered as a promising next‐generation NIR light sources.…”
Section: Introductionmentioning
confidence: 99%
“…As a new generation of luminescent materials, emerging metal halide perovskites/perovskite derivatives with unique photoluminescence (PL) properties have attracted growing research interests. [ 14–23 ] Many of high‐efficiency blue, green, yellow, red, and even single‐phase white emitting metal halides have been explored, in which the PL wavelength covering the entire visible light region can be controlled by assembling alkali metal cations or organic cations with different metal halide species. [ 24,25 ] Meanwhile, thanks to the low‐temperature solution processable characteristic and the great adjustability of emission, metal halides have also been considered as a promising next‐generation NIR light sources.…”
Section: Introductionmentioning
confidence: 99%
“…Connection of adjacent independent complex units via the π-π interactions of protonated 4HP ligands and hydrogen bonding interactions (N-H•••X) favors dense stacking, which somewhat impedes nonradiative decays and quenching by oxygen (Figure 1; Figure S3 and Table S3, Supporting Information). [40][41][42] The large steric hindrance imparted by two ZnCl 2 units connected to the binuclear complexes causes the distance of the two neighboring 4HP rings in binuclear complexes to be larger than that in mononuclear systems. [43] Moreover, the dihedral angles for binuclear complexes ZnCl 2 -B and ZnBr 2 -B are 10.08° and 4.74°, respectively, whereas those for mononuclear ZnCl 2 -G and ZnBr 2 -G are both 0°.…”
mentioning
confidence: 99%
“…Because of the larger tolerance of organic phosphors (such as tetraphenylphosphorous) and looser organic molecular accumulation alleviating the TTA process, 0D hybrid OIMHs can achieve high phosphorescent quantum yields of up to 63%. [ 26 ] The hybrid materials also provide an excellent platform for controlling the luminescent properties of inorganic metal halides. White and tunable emissions covering the whole visible spectrum can be realized by controlling the topological structures of metal halide‐emitting centers and changing the types of metal ions and halogens.…”
Section: Discussionmentioning
confidence: 99%
“…[ 52 ] Yan and coworkers used tetraphenylphosphorous units as organic phosphors combined with metal halide tetrahedral clusters and obtained a series of new 0D hybrid OIMHs, (Ph 4 P) 2 Cd 2 X 6 and (Ph 4 P) 2 CdX 4 (X = Br or Cl), through cocrystal assembly. [ 26 ] They found that the thermally activated delayed fluorescence (TADF) bands of organic phosphor could serve as energy buffer layers to compensate for the phosphorescence loss with the increase in temperature ( Figure ). As a result, this provided a new method to realize the zero‐temperature quenching of visible emissions over a wide range from 100 to 320 K. Furthermore, (Ph 4 P) 2 Cd 2 Br 6 showed a high phosphorescent quantum yield of 63%, which was a new record for the reported OIMHs with RTP (Table 1, Entry 21).…”
Section: Organic–inorganic Metal Halidesmentioning
confidence: 99%
See 1 more Smart Citation